Innovative Products Processed from Coconut and Nuts Sari Nadhi Business Learning Group in Carangsari Village Badung - I Wayan Sudiarta; A.A. Made Semariyani; Ni Made Ayu Suardani Singapurwa; Ni Made Darmadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Regional Featured Product Development Program activities in Carangsari Village, Petang, Badung, and Bali were carried out at the Sari Nadhi Business Study Group. Coconuts into coconut oil have been produced and marketed by partners, but this has not been implemented. intensive, and partners want to have new superior products by processing local agricultural products, especially coconuts and nuts, to support the Carangsari Tourism Village. Partners do not know the field of business management, so they experience problems managing production and marketing. The solutions taken to overcome the problems faced by partners are: providing appropriate technology in the processing of coconut and nut-based products; storage and packaging; marketing; and business management; and assisting with processing equipment and business capital. The output target that has been achieved is Appropriate Technology for Processing Coconuts and Nuts.